2008
DOI: 10.12702/1984-7033.v08n04a01
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stratification based on a 28 x 28 diallel of open-pollinated maize varieties

Abstract: -The objective of this study was to assess the representativeness of the test environments used by the maize breeding program of Embrapa in the first (1991-92 and 1992-93), at three locations (Sete Lagoas, MG, Londrina, PR, and Goiania-GO); in two growing seasons (1991/92 and 1993/94) in Aracaju-SE; and in two growing seasons (1992-93 and 1993-94) , in Ponta Grossa-PR. The complex part of the interaction accounted for nearly 75% of the genotype by environment interaction (G x E). The environments of Londrina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Garbuglio et al (2007) in a study with 27 maize cultivars in 22 environments, found in 87% of pairs of environments G×E interactions with predominance of complex part and 56% with low magnitude of Pearson correlations. Pacheco et al (2008) verified in ten environments, working with a diallel cross involving 28 open-pollinated maize populations, which was predominant in 100% of the interaction pairs of the complex part. Ribeiro and Almeida (2011), analyzing two sets of genotypes (sets 1 and 2) in ten environments in the states of Paraná, Minas Gerais and Bahia, revealed predominantly complex interactions in 96% and 100% pairs of environments, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Garbuglio et al (2007) in a study with 27 maize cultivars in 22 environments, found in 87% of pairs of environments G×E interactions with predominance of complex part and 56% with low magnitude of Pearson correlations. Pacheco et al (2008) verified in ten environments, working with a diallel cross involving 28 open-pollinated maize populations, which was predominant in 100% of the interaction pairs of the complex part. Ribeiro and Almeida (2011), analyzing two sets of genotypes (sets 1 and 2) in ten environments in the states of Paraná, Minas Gerais and Bahia, revealed predominantly complex interactions in 96% and 100% pairs of environments, respectively.…”
Section: Resultsmentioning
confidence: 92%